Effect of Chitosan on the Performance of NiMoP-Supported Catalysts for the Hydrodesulfurization of Dibenzothiophene. (18th February 2016) - Ríos-Caloch, Guillermina; Santes, Víctor; Escobar, José; Pérez-Romo, Patricia; Díaz, Leonardo; Lartundo-Rojas, Luis
Abstract : Chitosan-added NiMoP catalysts supported on alumina and alumina-titania were studied in the hydrodesulfurization (HDS) of dibenzothiophene (DBT). The preparation of catalysts containing Mo (12 wt%), Ni (3 wt%), P (1.6 wt%), and chitosan/nickel = 2 (mol ratio) was accomplished by sequential pore-filling impregnation varying the order of chitosan integration. Materials were characterized by DRIFTS, TPR, TG-DTA, and XPS techniques. The TG-DTA study showed that the nature of the support influences the degradation of chitosan onto the catalytic materials and also influences the HDS of DBT and the product distribution as well. The series of catalysts supported on alumina presented the most remarkable effect of chitosan, in which the OH and NH groups of the organic molecule interact with acid sites of the support weakening the interaction between alumina and deposited metal phases. In all cases, DBT was converted mainly through direct sulfur removal. The catalysts ChP3/A (alumina support impregnated with chitosan in phosphoric acid solution, prior to NiMoP deposition) and ChP4/AT (alumina-titania support impregnated with NiMoP solution, prior to contacting with a solution comprising chitosan and phosphorus) exhibited the best performance in HDS reactions and also showed the highest selectivity in biphenyl formation. Presence of carbonaceous residua on the catalyst's surface, as shown by XPS, could enhance the HDS activity over the ChP4/AT sample.